The Role of Organizational Communication for the Optimization of BUMDes in Soket Laok Village, Bangkalan Regency, Madura - Rachmah Ida; Angga Prawadika Aji; Titik Puji Rahayu; Ratih Puspa; Yuyun Wahyu Izzati Surya; Nisa Kurnia Ilahiati; Liestianingsih Dwi Dayanti (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: BUMDES management is a crucial part of managing village development and independence. Therefore, the management system of village government organizations must begin to be addressed because of its crucial position in the preparation of plans for the establishment of the BUMDES program. The inability to develop organizational systems that understand managerial principles, data management, and communication strategies coupled with unpreparedness to adapt to the development of internet technology has the potential to cause the organization to lag behind in developing. Objective: The aim of this study is to increase the potential of Soket Laok Village, Bangkalan Madura Regency in the field of BUMDES management. Method: This community service was held at the Soket Laok Village Hall, Bangkalan Madura Regency. The material was delivered in a hybrid manner where there are speakers who directly invite participants to practice and online participants who provide material at the beginning. Results: The village officials and community leaders understand and are brave enough to formulate village development plans and have a better understanding of good communication patterns. Conclusion: The introduction and understanding of organizational communication for BUMDes (Village Owned Enterprises) which is the central organization of economic empowerment of rural communities is significant. With the FGD method directly with the BUMDes manager in Soket Laok village, Bangkalan Madura, and socialization of practical knowledge, understanding and management of the BUMDes organization, the optimization of the role of BUMDes in the Soket Laok village community will occur.